1992
DOI: 10.1084/jem.176.3.915
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of proliferation of normal and transformed neural cells by blood group-related oligosaccharides.

Abstract: SummaryA synthetic tetrasaccharide structurally related to blood groups and sdectin ligands inhibited division of astrocytes, gliomas, and neuroblastomas at rnicromolar concentrationi The compound was cytostatic for primary astrocytes in culture, but cytotoxic for fast proliferating cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…An overall inhibitory eect on cell proliferation is the rule, but a stimulatory eect on SK-UT-1 growth was observed with PAA-A (0.5 lg/ml and 50 lg/ ml) at the end of the culture. Interestingly enough, a tetrasaccharide related to histo-blood-groups A and Le d has been demonstrated as reducing proliferation in astrocytes, gliomas and neuroblastomas at micromolar concentrations (Santos-Benito et al 1992). Although blood-group oligosaccharides have been known for a long time, their biological role has not been fully established.…”
Section: Discussionmentioning
confidence: 98%
“…An overall inhibitory eect on cell proliferation is the rule, but a stimulatory eect on SK-UT-1 growth was observed with PAA-A (0.5 lg/ml and 50 lg/ ml) at the end of the culture. Interestingly enough, a tetrasaccharide related to histo-blood-groups A and Le d has been demonstrated as reducing proliferation in astrocytes, gliomas and neuroblastomas at micromolar concentrations (Santos-Benito et al 1992). Although blood-group oligosaccharides have been known for a long time, their biological role has not been fully established.…”
Section: Discussionmentioning
confidence: 98%
“…It inhibited the proliferation in culture of both primary astroblasts and glioma cells (both rodent and human) at nanomolar concentrations, both in defined medium or in the presence of 10% foetal calf serum. Synthetic oligosaccharide analogues of neurostatin inhibited the division of astroblast, glioma and neuroblastoma cells in culture358,359 and promoted the destruction in vivo of an experimental rat brain glioma 360. Compounds like neurostatin probably arrest glioma growth by direct antimitotic action on the tumoral cells, affecting lipid raft microdomains and interfering with multiple signals regulating cell cycle progression (Fig.…”
Section: Making Glioma Immunodetectablementioning
confidence: 99%
“…9). It was the best first generation synthetic inhibitor of astroblast and astrocytoma growth, designed based on its immunological properties before neurostatin structure was known 358,359. TS4 inhibited the proliferation of C6 rat glioma cells in culture, as well as the growth of brain tumors formed after intracerebral transplantation of C6 cells 360.…”
Section: Making Glioma Immunodetectablementioning
confidence: 99%
“…2 On the basis of structural elements of the natural inhibitor, we synthesized series of oligo-and monosaccharides, which were tested as inhibitors of brain tumor cell division. [3][4][5][6][7] Recently we have obtained a family of N-acyl-glucosamine derivatives, some of which showed antimitotic activity against rat C6 glioma cells with low IC 50 values. 7 The results obtained indicated that the activity was increased by a long hydrocarbon chain at position C-1 of the glucosamine backbone, the most inhibitory compound being the oleyl glycoside 1 (Chart 1).…”
Section: Introductionmentioning
confidence: 99%